2020
DOI: 10.1021/acs.jafc.0c06426
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Apple Phlorizin Attenuates the Redox State Related to Gut Microbiota Homeostasis in C57BL/6J Mice Fed with a High-Fat Diet

Abstract: We explored the effects of dietary supplementation with phlorizin on redox state-related gut microbiota homeostasis in an obesity mouse model. Mice (C57BL/6J) were grouped as follows for 12 weeks: normal chow diet group (NCD), high-fat and cholesterol diet group (HFD), and treatment groups fed with HFD along with three levels of phlorizin. Phlorizin alleviated the hyperlipidemia and redox status and increased the total ccal SCFA content (1.88 ± 0.25 mg/g). Additionally, phlorizin regulated gene expression rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Information on the vitamin mix, mineral mix, casein, lard, corn starch, sucrose, gelatin, formic acid, acetonitrile, and other reagents was mentioned in our previous study (Liu, Ji, Guo, et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the vitamin mix, mineral mix, casein, lard, corn starch, sucrose, gelatin, formic acid, acetonitrile, and other reagents was mentioned in our previous study (Liu, Ji, Guo, et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the concentrated and lyophilized eluent was purified with ethyl acetate, and the yield of PSPAE was approximately 0.23 g from 100 g raw purple sweet potato (approximately 0.71 g per 100 g dry weight powder). Information on the vitamin mix, mineral mix, casein, lard, corn starch, sucrose, gelatin, formic acid, acetonitrile, and other reagents was mentioned in our previous study (Liu, Ji, Guo, et al, 2021).…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…These results suggested that the administration of FLRB could increase the content of SCFAs in diabetic mice and might account for the change in gut microbiota in this study. SCFAs were proven to play a crucial role in gut barrier function by improving epithelial growth and can impede appetite by upregulating several proteins related to satiety, and they were closely correlated with the structure of intestinal microbes ( Kim et al, 2018 ; Liu et al, 2021 ). In our study, we showed that the treatment of defatted rice bran fermentation extracts not only enriched SCFA-producing bacteria but also increased the content of SCFAs in diabetic mice, suggesting that the major modulation of intestinal microbes may occur by changing the production of SCFAs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these results suggested that the gut microbiota played key roles in the development of T2DM. Short-chain fatty acid (SCFA), generated from undigested carbohydrates by gut microbiota, strengthen gut barrier function by supporting energy for epithelial growth and resisting invading microbes ( Wang Y. X. et al, 2020 ; Liu et al, 2021 ). Moreover, SCFAs can regulate the relative expression of proteins controlling satiety and then reduce appetite to improve T2DM ( Kim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The byproducts of lipid metabolism in a HFD would injure the mucosa of the large intestine and decrease the mucosal thickness of the cecum ( Yang et al, 2021 ). A recent report has shown that infiltration of inflammatory cells, ulceration, and epithelial damage were also detected in the cecum and colon of mice fed with HFD ( Liu et al, 2021 ). In addition, gut microbiota mainly in cecum and colon could utilize dietary fiber or other macromolecule, which is not digested by host enzyme, to produce some effective metabolites ( Koh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%